Կոռուպցիայի ազդեցությունը կառավարման արդյունավետության վրա - Ավետիսյան, Գեորգի (Bulletin of Yerevan University G: Economics, 2017)
In the article, certain corruption level assessments in dynamics in RA, as well as certain comparative analyses between some CIS and Eastern European countries, are illustrated. The analysis enables to reveal the impact of corruption perceptions index on governance efficiency. To overcome the negative effect of the latter, some policy recommendations are stated.
Keywords: corruption, corruption perceptions index, governance efficiency, econometric estimation, panel data